2008
DOI: 10.1007/s11259-008-9185-0
|View full text |Cite
|
Sign up to set email alerts
|

Macroanatomy of coronary arteries in Bactrian camel (Camelus bactrianus)

Abstract: The aim of present study was to determine the origin, distribution and course of the coronary arteries in Bactrian camels. Ten hearts of adult healthy Bactrian camels of different sex constituted the material. Following exposition of the arteries by means of injection of 15% ABS coloured with red carmine to a. coronaria sinistra and a. coronaria dextra, dissection was performed. The arterial vascularization of the heart in Bactrian camels was determined to be supplied by a. coronaria sinistra and a. coronaria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
23
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 8 publications
7
23
2
5
Order By: Relevance
“…Tecirlioğlu ve ark. [3] , ile Karadağ ve Soygüder'in [5] bildirdiği gibi a. coronaria sinistra'nın, çok sayıda atrial ve ventriküler dalı olan r. circumflexus sinister'e, Literatürde [18,20,[27][28][29] r. interventricularis subsinuosus'un a. coronaria dextra'dan orijin aldığını bildirilmiştir. Fakat Zavot ırkı sığırlarda r. interventricularis subsinuosus'un a. coronaria sinistra'nın sulcus interventricularis subsinuosus içerisinde devamı eden bir kolu olduğu belirlendi.…”
Section: Tartişma Ve Sonuçunclassified
See 3 more Smart Citations
“…Tecirlioğlu ve ark. [3] , ile Karadağ ve Soygüder'in [5] bildirdiği gibi a. coronaria sinistra'nın, çok sayıda atrial ve ventriküler dalı olan r. circumflexus sinister'e, Literatürde [18,20,[27][28][29] r. interventricularis subsinuosus'un a. coronaria dextra'dan orijin aldığını bildirilmiştir. Fakat Zavot ırkı sığırlarda r. interventricularis subsinuosus'un a. coronaria sinistra'nın sulcus interventricularis subsinuosus içerisinde devamı eden bir kolu olduğu belirlendi.…”
Section: Tartişma Ve Sonuçunclassified
“…[18] , Yuan ve ark. [28] , Tıpırdamaz'ın [30] çalışmalarındaki bilgilere paralel olarak araştırmamızda r. proximalis atrii sinistri'nin r. circumflexus sinister'den orijin aldığı tespit edildi. Ancak Doğruer ve Özmen [15] çalışmalarında 9 kalpte, Tecirlioğlu ve ark.…”
Section: Tartişma Ve Sonuçunclassified
See 2 more Smart Citations
“…Our previous study had reported the origin, distribution and course of the coronary arteries in Bactrian camels on gross examination (Yuan et al, 2009). However, much less is known of the ultrastructure of the coronary artery endothelium.…”
Section: Introductionmentioning
confidence: 99%